Development Of Early Childhood Creativity With Physical Motor Skills Using Project-Based Learning At Cemara Liliba Kindergarten - Orvinanto Sabneno; Adriana Lape; Fenti Bani; Yuni Hano; Maria Fahik; Defrin Waang; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Creativity is a fundamental aspect of early childhood development because it supports children's ability to generate ideas, solve problems, and express themselves through meaningful learning experiences. However, empirical evidence regarding the implementation of Project-Based Learning using an ex post facto design in authentic early childhood classroom settings remains limited. Objective: This study aimed to examine the effect of Project-Based Learning on the creativity development of children aged 5–6 years at Cemara Liliba Kindergarten. Method: A quantitative approach with an ex post facto design was employed involving 20 children selected through purposive sampling. Data were collected using Project-Based Learning and creativity instruments based on relevant theoretical indicators and analyzed using descriptive statistics and simple linear regression. Results: The findings revealed that Project-Based Learning had a positive and significant effect on children's creativity development, with an R Square value of 0.304, indicating a contribution of 30.4%. The implementation of mindful, meaningful, and joyful learning activities also supported children's active engagement during project-based learning. Novelty: This study provides empirical evidence of the effectiveness of Project-Based Learning in enhancing early childhood creativity through an ex post facto design in an authentic classroom context. Conclusion: Consistent implementation of Project-Based Learning can effectively foster children's creativity and provide practical guidance for teachers in designing meaningful, child-centered learning experiences.